Little girl with a doll and teenage girls standing by a jungle gym - Unknown:::Creator::::::::::::
Photograph shows a little girl and a couple of teenage girls standing by a jungle gym at a playground. The little girl is holding a doll. This is probably part of the Campbell Y-Teens Camper Counselor Recreation Program in 1962.